Anti-biofilm peptide combinations against Pseudomonas aeruginosa and Staphylococcus aureus - Jorge, Paula Alexandra Silva (2014)
Today, we are facing a major challenge regarding the development of new strategies and the discovery of new compounds with effective antimicrobial outcomes. The emergence of resistance is a preoccupant health threat and conventional antibiotics are being rendered ineffective [1]. Specifically, biofilm related infections are becoming a serious threat, being highly related to chronic infections but also nosocomial and biomaterial related infections, and they are considered the major cause of dissemination of antibiotic resistance in the nosocomial scenario. Researchers are now focusing in alternatives, such as the discovery of new antimicrobials with different modes of action, and the combination of agents potentiating their efficacy. AMPs are an example of new antimicrobials with promising applications, since they have different and sometimes unspecific mechanisms of action compared to traditional antibiotics, reducing the chance of acquired resistance, and are showing promising results in the biofilm area. A growing interest has been emerging for the use of antimicrobial combinations as a strategy to increase the antimicrobial spectrum, prevent the emergence of resistance, reduce toxicity and side effects and provide synergistic activity. Because of this, in this work we analyse AMP combinations against major pathogenic bacteria, Pseudomonas aeruginosa and Staphylococcus aureus, currently great contributors for resistance development and responsible for chronic infections, such as cystic fibrosis pneumonia. We present a screening of combinations of the AMP antibiotic colistin with the AMPs temporin A, citropin 1.1 and tachyplesin I against these pathogens, including references and clinical isolated strains. Planktonic and biofilm mode of growth were implemented and results show that most combinations have addictive and synergetic activities, including total inhibition of biofilm formation for some of the combinations tested. This means that AMP combinations should be a viable way for the development of new antimicrobial treatments, thus reducing their toxicity and side effects, while maintaining efficacy.